Hydrothermal growth of n-ZnO films on a patterned p-GaN epilayer and its application in heterojunction light-emitting diodes. (22nd February 2017) - Ko, Rong-Ming; Wang, Shui-Jinn; Chen, Ching-Yi; Wu, Cheng-Han; Lin, Yan-Ru; Lo, Hsin-Ming
Abstract: The hydrothermal growth (HTG) of crystalline n-ZnO films on both the nonpatterned and patterned p-GaN epilayers with a honeycomb array of etched holes is demonstrated, and its application in n-ZnO/p-GaN heterojunction light-emitting diodes (HJ-LEDs) is reported. The results reveal that an HTG n-ZnO film on a patterned p-GaN layer exhibits a high-quality single crystal with FWHMs of 0.463 and 0.983° obtained from a ω-rocking curve and a ϕ-scan pattern, respectively, which are much better than those obtained on a nonpatterned p-GaN layer. In addition, the n-ZnO/patterned p-GaN HJ-LED exhibited a much better rectifying diode behavior owing to having a higher n-ZnO film crystallinity quality and an improved interface with the p-GaN layer. Strong violet and violet-blue lights emitted from the n-ZnO/patterned p-GaN HJ-LED at around 405, 412, and 430 nm were analyzed.